ABC-analysis of the Bachelor’s Educational Programs of Lesya Ukrainka Eastern European National University (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyzes 70 bachelor’s educational programs of Lesya Ukrainka Eastern European National University. For the study the ABC method is used, which divides the initial set of objects into three  subsets depending on their specific gravity in the total value of the indicator: A – approximately 75–80 %; B – approximately 10–15 %; C – approximately 5–10 %. The originality of the study is that the ABC-analysis was applied to an object such as a university. The table with the numbers of students enrolled in the first year of full-time study forms for obtaining a bachelor’s degree in higher educational institution was constructed. The groups A, B, C of the university’s educational programs are determined on the basis of income from tuition fees of first-year students. On the basis of the obtained results a rating of 15 faculties was formed. For the study the data by 2017 are used. To group A 26 (37,14 % of the total number) educational programs were allocated, with the share of which in the total amount of income from students enrolled in the first year of full-time education accounted for 79,82 %. In group B, 16 (22,86 % of the total number) educational programs were received. Their contribution to the total income was 15,09 %. Group C united 28 (40 % of the total number) educational programs, the share of which in the total amount of income was 5,09 %. The obtained results showed that 37,14 % of educational programs bring 79,82 % of the income from the training of fulltime freshmen. The most popular among students-payers are three faculties (foreign philology, law, international relations), which bring the university every more than 10 % of the income of all freshmen of full-time study forms. The results of the study can be used in planning of university vocational guidance work among students of the graduation classes of schools and students of vocational schools, advertising expenses. Further research can be done on the basis of master’s degree data.
Keywords: ABC-analysis, Lesya Ukrainka Eastern European National University, bachelor, educational program, tuition fee, faculty, rating.